Variability in histamine receptor genes HRH1, HRH2 and HRH4 in patients with hypersensitivity to NSAIDs. (November 2013) - Ayuso, Pedro; Blanca, Miguel; Cornejo-García, José A; Torres, María José; Doña, Inmaculada; Salas, María; Blanca-López, Natalia; Canto, Gabriela; Rondón, Carmen; Campo, Paloma; Laguna, José J; Fernández, Javier; et al.
Aim: Histamine plays an important role in the pathogenesis of allergic diseases. Genetic variations in histamine receptors (HRH) may influence the expression of allergic diseases. This study analyzes the association between HRH variants and NSAID hypersensitivity reactions.Patients & methods: The authors analyzed copy number variations (CNVs) and common functional SNPs in genes HRH1, HRH2 and HRH4 in 442 unrelated patients with hypersensitivity to NSAIDs and in 414 healthy unrelated controls.Results: The authors identified, both in patients and control subjects, individuals carrying CNVs in HRH genes. The most common genotype corresponded to two copies of each gene, but carriers of one or three copies of HRH1 (5% of individuals), HRH2 (1.1%) and HRH4 genes (0.9%) were also identified.Conclusion: For the first time, we describe CNVs in human HRH genes. Neither common functional SNPs in HRH genes nor CNVs influenced the risk of developing hypersensitivity to NSAIDs. Original submitted 31 May 2013; Revision submitted 7 August 2013